Constructed Wetland: A Solution for Wastewater Treatment - Shrestha, Dibesh; Maharjan, Shovana (Hydro Nepal: Journal of Water, Energy and Environment, 2010)
Due to population explosion, rapid industrialization and urbanization, Nepal's limited source of water is polluted (especially in the Kathmandu Valley). The quality of water is vital concern, as it is directly linked with human welfare. The water that we use for our survival should be potable, clean, and free of impurities. To mitigate the problem of water pollution, low-cost natural treatment options like Constructed Wetlands (CW) and the related Reed Bed Treatment System (RBT) have been introduced in Nepal in several places like hospitals, universities and other institutions, and as community systems. The plant species Phragmites karka is used in this process. It, and other associated micro organisms removes contaminates from wastewater using a natural process. Compared to other large and expensive technologies, CW and RBT require less land and are less expensive for construction, operation and maintenance. Hence, they can be considered as effective, economic and environmentally friendly and sustainable systems for wastewater treatment. Keywords: Wastewater treatment; Constructed Wetlands (CW); Reed Bed Treatment (RBT); Nepal DOI: 10.3126/hn.v5i0.2486 Hydro Nepal Vol. 5, July 2009 Page:42-45